Comparativo de Estratégias para Resposta a Emergências usando Redes Ad Hoc Veiculares e Computação em Névoa - Campos, Bruno P.; Henri, João; Batista, Daniel M.; Hirata Jr, R.; Ullah, Kifayat (Companion Proceedings of the Brazilian Symposium on Computer Networks and Distributed Systems (SBRC); 2023: Companion Proceedings of the 41st Brazilian Symposium on Computer Networks and Distributed Systems, 2023)
In extreme vehicular accidents, victims often fail to contact emergency response teams in time. Aiming to automate the accident detection and reporting process, this paper presents partial results of the comparison between different strategies to provide an emergency response that uses the communication capabilities of Vehicular Ad Hoc Networks (VANETs) assisted by fog computing to report emergencies with the help of an emergency response unit. Simulation experiments showed that some strategies were able to reduce the total emergency response time by up to 60.13%. The developed software is shared as open-source software, allowing the reproduction of experiments.